Thin lithium negative electrode adaptive to low-cost ester electrolyte, preparation method of thin lithium negative electrode and application of thin lithium negative electrode in lithium battery

Through chemical repair and chemical substitution methods, the lithium metal negative electrode is processed to generate a lithium-rich lithium-philic alloy interface, which solves the problems of uneven lithium deposition and lithium dendrites in the ester electrolyte, and achieves the effect of high cycle stability and capacity retention.

CN119601604APending Publication Date: 2025-03-11ZHENGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411879647.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When using ester electrolytes in existing lithium metal batteries, the lithium metal and the electrolyte undergo a violent chemical reaction, resulting in uneven deposition of lithium and the formation of lithium dendrites, which in turn causes low Coulomb efficiency, volume expansion and safety issues, limiting the development of lithium metal batteries.

Method used

The lithium foil is repaired by chemical repair method and chemically replaced in the lithium-philic metal salt solution to generate a lithium-rich lithium-philic alloy interface to improve lithium ion transport and reduce the formation of lithium dendrites.

Benefits of technology

Through chemical repair and chemical substitution methods, the cycle stability and capacity retention rate of lithium metal negative electrodes are significantly improved, and efficient and stable performance in traditional low-cost ester electrolytes is achieved, and it is suitable for soft-pack batteries and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601604A_ABST
    Figure CN119601604A_ABST
Patent Text Reader

Abstract

The invention discloses a thin lithium negative electrode adaptive to a traditional low-cost ester electrolyte, a preparation method of the thin lithium negative electrode and application of the thin lithium negative electrode in a lithium battery. A lithium-loving interface alloy layer is successfully prepared on thin lithium through a chemical repair method and a chemical replacement method at normal temperature. The modified lithium metal negative electrode has a significantly reduced polarization phenomenon, the low nucleation overpotential of the interface alloy layer promotes uniform initial lithium nucleation, it is guaranteed that lithium ions rapidly pass through the alloy layer, and the electroplating / stripping behavior of lithium is effectively adjusted. The modified lithium metal negative electrode has a relatively low ion diffusion barrier, and the insulation component in the alloy layer ensures rapid diffusion of lithium ions on the surface and inside of the negative electrode, so that dendritic crystal growth caused by non-uniform local ion distribution under high current density is inhibited. The invention provides a simple and promising surface engineering strategy, and provides a unique problem solving thought for the application of the modified lithium metal negative electrode in the lithium battery, so that the method for realizing long circulation under the lithium battery system is diversified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of high specific energy lithium metal batteries, and in particular relates to a thin lithium negative electrode adapted to a low-cost ester electrolyte, a preparation method thereof, and an application in a lithium battery. Background Art

[0002] The current commercial energy storage system can no longer meet the development needs of portable electronic devices, electric vehicles and smart grids. The development of high-performance rechargeable batteries is the key to promoting the development of high-energy density batteries. In recent years, lithium metal batteries have been widely used due to their ultra-high theoretical specific capacity, extremely low redox potential and lightest metal mass (3860 mAh g −1 , −3.04 Vvs standard hydrogen electrode, 0.534 g cm −3 ), has become one of the current research hotspots. In particular, the lithium metal anode is matched with the nickel-rich layered cathode LiNi x Mn y Co 1−x−y O2, such as LiNi 0.8 Mn 0.1 Co 0.1 O2 (NMC811) is one of the most effective material combinations for rechargeable batteries. However, when matching traditional commercial electrolytes under the current positive and negative electrode systems, although the layered positive electrode material has good compatibility with it, lithium metal will undergo violent chemical reactions with most organic electrolytes, especially in carbonate-based electrolytes. The unevenness of lithium deposition and the high reactivity with ester electrolytes lead to the generation of a large number of lithium dendrites at the lithium metal negative electrode during the charge and discharge cycle, which in turn leads to problems such as low Coulomb efficiency, rapid volume expansion and industrial safety, making the development of lithium metal batteries face huge challenges.

[0003] Artificial coatings, which have developed rapidly in recent years, are often based on improvement methods for thick lithium electrodes (>50 µm). The thickness of the electrode greatly affects the performance of the battery in many key aspects, such as energy density, capacity decay rate, heat dissipation effect, etc. At present, there are many strategies for manufacturing thick positive electrodes, such as magnetic arrangement methods and gradient electrode design. The application of thin lithium anodes improves the overall energy density of the battery, but it still faces the common problems of lithium metal anodes, and due to its thinner thickness, it also has the problem of poor mechanical properties. Therefore, before the large-scale application of lithium metal anodes, major safety challenges must be overcome, especially those related to lithium dendrite growth and unstable artificial solid electrolyte interface (SEI) films. Therefore, designing an artificial SEI or interface protection layer with excellent stability on a thin lithium anode is the key to achieving high-performance lithium metal batteries.

[0004] Patent CN 118315689 A discloses an organic-inorganic composite protective layer for lithium metal negative electrode and its preparation method and application, wherein an inorganic protective layer is generated by in-situ reaction of metal fluoride and lithium, and then a cross-linked polyethylene glycol ester organic compound is applied to form a composite protective layer for lithium metal negative electrode and battery. However, the patent does not conduct an in-depth study on the influence of metal fluoride selection on the performance of the composite protective layer, especially the insoluble nature of fluoride may lead to uneven reaction and affect the quality of the protective layer; and does not fully consider the influence of residual solute solvent and side reactions that are not removed in large-scale production on battery performance.

[0005] Patent CN 113629236 B discloses a composite metal lithium negative electrode and its preparation method and application. The negative electrode includes a three-dimensional carbon-based current collector, metal lithium and a protective film containing a lithium-philic metal and a lithium salt, which is prepared by pre-treating the current collector with a lithium-philic metal salt and then compounding it with molten metal lithium. However, the patent does not fully consider the problems that may arise in large-scale production or expansion to soft-pack batteries, such as further cost optimization and process stability; there is a lack of more in-depth research on the long-term stability and interaction between the protective film and the metal lithium and the current collector, which limits the improvement of battery performance and the wide application of technology.

[0006] In the context of existing technologies, although some research progress has been made in the negative electrode protection strategy for the purpose of inhibiting lithium dendrites, most of the research is based on small button batteries with a capacity of milliampere hours. When it is enlarged to ampere-hour soft-pack batteries, its effectiveness and the practical problems it faces are still unknown. On the one hand, the problem of poor compatibility between thin lithium negative electrodes and ester electrolytes has not been properly solved. Whether through special structural design or material modification, it is still difficult to achieve efficient and stable performance in the soft-pack battery system. On the other hand, some existing thick lithium negative electrode improvement strategies, such as the methods presented in some patents, have problems such as complex processes, high costs, and difficulty in large-scale production in actual soft-pack battery application scenarios, and the improvement in the overall performance of the battery is limited. Summary of the invention

[0007] In view of the above problems, the present invention provides a thin lithium negative electrode suitable for low-cost ester electrolyte, a preparation method thereof and application in a lithium battery.

[0008] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a thin lithium negative electrode suitable for a low-cost ester electrolyte comprises the following steps: chemically repairing a lithium foil using a chemical repair agent, immersing the chemically repaired lithium foil in a lithium-philic metal salt solution for chemical replacement, washing, and drying to obtain a lithium metal negative electrode having a lithium-philic interface alloy phase.

[0009] Furthermore, the chemical repair agent is any one of polar solvents such as dimethyl sulfoxide, tetrahydrofuran, N-methylformamide, N,N-dimethylformamide, acetone, acetonitrile and fluoroacetonitrile, or a mixture of two or more of them in any proportion, and the chemical repair agent needs to be dried before use. While removing the thin lithium surface oxidation passivation layer, it will not have a destructive reaction with the thin lithium, and make the subsequent chemical replacement more dense and uniform.

[0010] Furthermore, the lithium-philic metal salt in the lithium-philic metal salt solution is any one of TiCl4, InCl3, In(NO3)3 and Cu(NO3)2, or a combination of two or more thereof; the lithium-philic metal salt solution and the solvent used for cleaning are any one of ethylene glycol dimethyl ether, dodecyl ether, cyclopentyl methyl ether, 1,3-dioxolane, ethylene carbonate and ethyl methyl carbonate, or a combination of two or more thereof, and the lithium-philic metal salt and solvent must be dried before use.

[0011] The drying of the repair agent or solvent refers to adding the dried molecular sieve into the repair agent or solvent to remove water for 48h~72h; the drying of the molecular sieve refers to placing the molecular sieve at 250~350℃ and drying it for 3~4h.

[0012] Drying the lithium-philic metal salt refers to drying the lithium-philic metal salt in a vacuum environment at 100-150° C. for 10-30 hours.

[0013] Furthermore, the concentration of the lithium-philic metal salt in the lithium-philic metal salt solution is 1-100 mM, and the time of chemical replacement is 1-60 minutes.

[0014] Furthermore, the time of chemical repair is 0.2~2 h.

[0015] Furthermore, chemical repair, chemical replacement, and drying were all performed in an argon-filled glove box (oxygen <1 ppm, water <1 ppm).

[0016] The thickness of the lithium foil is 20-50 microns, the thickness of the protective layer is 1-10 microns, and the lithium foil is loaded on the copper foil.

[0017] The thin lithium negative electrode prepared by the above preparation method is compatible with traditional low-cost ester electrolyte.

[0018] The application of the above-mentioned lithium negative electrode adapted to low-cost ester electrolyte in a lithium metal battery comprises a positive electrode, the above-mentioned lithium metal negative electrode, a separator and an ester electrolyte, wherein the lithium salt in the ester electrolyte is one or more of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide and lithium tris(trifluoromethylsulfonyl)methyl; the solvent in the ester electrolyte is one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, fluoroethylene carbonate, ethyl methyl carbonate, vinylene carbonate or dimethyl carbonate; the concentration of the lithium salt in the solvent is 0.5~4 mol / L.

[0019] Furthermore, the lithium metal battery is a symmetrical battery, a full battery or a soft pack battery, wherein one of the electrolytes is a 1M LiPF6 EC+EMC electrolyte, and the volume ratio of EC to EMC is 3:7 (1M LiPF6in EC:EMC (3:7) with 2%VC).

[0020] Furthermore, when the lithium metal battery is a full battery or a soft pack battery, the positive electrode loading is 20-25 mg cm −2 High nickel ternary material LiNi 0.83 Mn 0.12 Co 0.05 The assembly of O2, symmetric cells and full cells was carried out in a glove box filled with argon, and the assembly of soft-pack cells was carried out in a dry room with a moisture content of less than 1‰.

[0021] The beneficial effects of the present invention are: chemical repair simply and effectively removes the surface oxide layer and impurities of lithium metal generated by storage in a glove box or dry room. The in-situ spontaneous reaction between lithium and lithium-philic chloride or nitrate generates a lithium-rich lithium-philic alloy interface, which realizes rapid lithium ion transport and uniform lithium deposition without dendrites, thereby significantly improving the cycle stability (taking TiCl4 as an example, the symmetrical battery at 2.0 mA cm −2 , 2.0 mAh cm −2 The capacity of the modified full battery is 5.74 Ah, the N / P ratio is as low as 1.02, and the lean electrolyte is 1.75g ​​Ah. −1 400 Wh kg −1The soft-pack battery still showed a capacity retention rate of 96.04% after 100 cycles. The present invention provides a simple and promising surface engineering strategy, and inspires the design of thin lithium negative electrode protection that can achieve stable cycling in traditional low-cost carbonate electrolytes, providing a unique solution for the application of modified lithium metal negative electrodes in soft-pack batteries, and diversifying the methods for achieving long cycles in high-energy-density battery systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the preparation of a new thin lithium negative electrode.

[0023] Figure 2 The following are scanned photos of comparative examples, Example 1 and Example 4. (a) is a scanned photo of a bare lithium surface, (b) is a scanned photo of the surface of the lithium metal negative electrode of Example 1 after chemical repair, (c) is a scanned photo of the surface of the novel lithium metal negative electrode of Example 4 after chemical replacement, and (d) is a scanned photo of the cross section of the novel lithium metal negative electrode of Example 4 having a lithium-rich lithium-philic alloy interface.

[0024] Figure 3 2 are the time-voltage curves of the LiǁLi symmetric batteries of the comparative example and embodiment 4.

[0025] Figure 4 Scanning photos of (a) the comparative example and (b) the LiǁLi symmetric battery of Example 5 after 100 h of electroplating / stripping.

[0026] Figure 5 Comparative Example and Example 4 in LiǁLiNi 0.83 Mn 0.12 Co 0.05 Electrochemical impedance spectroscopy (EIS) graph in an O2 battery.

[0027] Figure 6 Comparative Example and Example 5 in LiǁLiNi 0.83 Mn 0.12 Co 0.05 Long-cycle performance diagram in O2 battery.

[0028] Figure 7 (a) Comparative Example and (b) Example 5 in LiǁLiNi 0.83 Mn 0.12 Co 0.05 Charge and discharge curves of different cycles in O2 battery.

[0029] Figure 8 The comparative example and Example 4 were at 400 Wh kg −1 Long cycle performance diagram of soft pack battery. The embedded picture is an optical photo of the finished soft pack battery.

[0030] Fig. 9 It is a reaction mechanism diagram of the comparative example and Example 4 during the electroplating process. DETAILED DESCRIPTION

[0031] The embodiment is a novel thin lithium anode with a lithium-rich, lithiophilic alloy interface.

[0032] (I) The preparation method is as follows: Figure 1 shown): 1. Preparation of Lithium Metal Anode without Surface Oxide Layer The present invention first obtains a lithium metal negative electrode with a clean and uniform surface by a chemical repair method: Example 1 The 4Å molecular sieve was placed in a muffle furnace and heated to 300°C to bake and remove water for 2 h. It was then transferred to a glove box filled with argon (oxygen <1 ppm and water <1 ppm) while hot. After cooling to room temperature, the molecular sieve was placed in dimethyl sulfoxide (DMSO) to remove water for three days. Subsequently, the lithium foil (lithium foil has a diameter of about 16 mm and a thickness of about 50 μm, and the lithium foil is loaded on copper foil) was placed in the dehydrated DMSO and fully immersed for 0.5 h for chemical repair to remove the oxide layer generated on the surface of the lithium foil during storage. Figure 2 As shown in (a), the surface scratches produced by the lithium foil during production, scraping or rolling, and the surface oxidation produced during transportation or long-term storage are clearly visible. Figure 2 As shown in (b), the surface is smooth and clean with no oxidizing substances present.

[0033] Example 2 The dried 4Å molecular sieve was placed in acetone to remove water for two days, and then the lithium foil (the diameter of the lithium foil was about 16 mm, the thickness was about 20 μm, and the lithium foil was loaded on the copper foil) was immersed in the dehydrated acetone for 0.2 h for chemical repair to remove the oxide layer generated on the surface of the lithium foil during the storage process.

[0034] Example 3 The dried 4Å molecular sieve was placed in tetrahydrofuran (THF) to remove water for two days, and then the lithium foil (the diameter of the lithium foil was about 16 mm, the thickness was about 30 μm, and the lithium foil was loaded on the copper foil) was immersed in the dehydrated THF for 2 h for chemical repair to remove the oxide layer generated on the surface of the lithium foil during the storage process.

[0035] In particular, similar effects can be achieved by replacing the above-mentioned chemical repair agents such as DMSO, acetone and THF with strong polar solvents such as N-methylformamide, N,N-dimethylformamide, acetonitrile and fluoroacetonitrile, and adjusting the repair time.

[0036] 2. Preparation of Lithium Metal Anode with Interface Protection Layer The present invention obtains a novel thin lithium negative electrode having a lithium-philic interface alloy phase by chemical replacement method: Example 4 Weigh an appropriate amount of TiCl4 and place it in a 110℃ oven under vacuum and heat for 12 h. After cooling to room temperature, transfer it to a glove box for use. At the same time, place an appropriate amount of dried 4Å molecular sieve in a non-protonic solvent of DME (ethylene glycol dimethyl ether) to remove water for three days. Slowly add the dried TiCl4 into DME (300 mL) and stir at room temperature for 3 hours to prepare a TiCl4 solution with a concentration of 5 mM. Immerse the chemically repaired lithium foil in a 5 mM TiCl4 DME solution for reaction for 3 minutes, then rinse the reacted lithium metal anode with dehydrated DME to remove residual TiCl4 on the surface, and dry it in an argon-filled glove box overnight. Finally, the thickness of the lithium-rich lithium-philic alloy interface layer is 8.2 μm. (Morphology as shown Figure 2 (c), thickness as Figure 2 (d)).

[0037] Example 5 Weigh an appropriate amount of ‌Cu(NO3)2 and place it in a 120℃ oven under vacuum and heat for 24 h. After cooling to room temperature, transfer it to a glove box for use. At the same time, place an appropriate amount of dried 4Å molecular sieve in an aprotic solvent of ethylene carbonate to remove water for two days. Slowly add the dried ‌Cu(NO3)2 into ethylene carbonate (300 mL) and stir at room temperature for 1 hour to prepare a ‌Cu(NO3)2 solution with a concentration of 20 mM. Immerse the chemically repaired lithium foil in a 20 mM ‌Cu(NO3)2 ethylene carbonate solution for reaction for 1 minute, then rinse the reacted lithium metal anode with dehydrated ethylene carbonate to remove the residual ‌Cu(NO3)2 on the surface, and dry it in an argon-filled glove box overnight to finally obtain a lithium-rich lithium-philic alloy interface layer.

[0038] In particular, the chemical replacement solutes TiCl4‌ and Cu(NO3)2 are replaced with any one or a combination of two or more of lithium-philic chlorides or nitrates such as InCl3 and In(NO3)3, and the solution concentration is adjusted to achieve similar effects. The solvents ethylene glycol dimethyl ether and ethylene carbonate used for chemical replacement are replaced with any one or a combination of two or more of aprotic solvents such as dodecyl ether, cyclopentyl methyl ether, 1,3-dioxolane, and ethyl methyl carbonate, and the reaction time is adjusted to achieve similar effects.

[0039] For the convenience of writing, the present invention refers to the lithium foil without any operation and the corresponding assembled battery as comparative examples, and the lithium foil after chemical repair and chemical replacement and the corresponding assembled battery as embodiments.

[0040] Taking the thin lithium negative electrode of Example 4 as an example, the assembly order of the symmetrical battery is to place the 2016 positive electrode shell, the thin lithium negative electrode of Example 4, the PP / PE / PP composite separator, 50 microliters of 1M LiPF6 EC / EMC (v / v = 3:7) and an electrolyte containing 2% VC, the thin lithium negative electrode of Example 4, the gasket and the 2016 negative electrode shell. When assembling the symmetrical battery of the comparative example and Example 5, refer to the above order, and only need to replace the thin lithium negative electrode of Example 4 with a bare lithium negative electrode or the thin lithium negative electrode of Example 5.

[0041] Ternary cathode LiNi 0.83 Mn 0.12 Co 0.05 The preparation process of O2 is as follows: 0.83 Mn 0.12 Co 0.05 O2, conductive carbon black (super P Li) and binder (PVDF) were mixed evenly in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) was poured into the mixture and stirred evenly. The mixture was then coated on aluminum foil using a coating machine to control the LiNi 0.83 Mn 0.12 Co 0.05 The loading amount of O2, conductive carbon black and binder is 20~25 mg cm −2 The coated rolled pole piece is placed in a vacuum drying oven at 80°C for 1 to 3 days and cut into the pole piece size required for the full battery or soft pack battery for use.

[0042] The full battery is assembled according to the 2016 positive electrode shell, with a diameter of 19 mm and a thickness of 8 microns. 0.83 Mn 0.12 Co 0.05 O2 ternary positive electrode, PP / PE / PP composite separator, 50 μL of 1M LiPF6 in EC / EMC (v / v = 3:7) and electrolyte containing 2% VC, Example 5 thin lithium negative electrode, gasket and 2016 negative electrode shell were placed in the order of assembling the full battery.

[0043] The thin lithium negative electrode of Example 4 or the thin lithium negative electrode of Example 5 was replaced with lithium foil without any operation as the negative electrode to assemble into a full battery of the control group.

[0044] (II) Test results: Figure 3 The time-voltage curves of the LiǁLi symmetric battery of the comparative example and Example 4. When the EC / EMC (v / v = 3:7) matching 1M LiPF6 and the electrolyte containing 2% VC are used, the current density is 2.0 mA cm −2 , with an area capacity of 2.0 mAh cm −2Under the above conditions, a Li / Li symmetrical cell was assembled using lithium foil without any operation as a comparative example to evaluate the electrolyte blocking characteristics and long-term cycle stability of the lithium-rich lithium-philic alloy interface layer. Example 4 still showed excellent stability after 400 hours, but the cell potential of the Li / Li symmetrical cell assembled using bare lithium as an electrode was polarized violently in the early stage of the stability test, and a transient short circuit occurred only after 125 hours. Importantly, the modified thin lithium negative electrode of Example 4 has significantly reduced polarization, and the low nucleation overpotential of the interface alloy layer promotes uniform initial lithium nucleation, ensures that lithium ions pass through the alloy layer quickly, and effectively regulates the lithium plating / stripping behavior.

[0045] Figure 4 The following are scanned photos of the front side of the electrode of (a) the comparative example and (b) the LiǁLi symmetric battery of Example 5 after 100 h of electroplating / stripping. Figure 4 As shown, at a current density of 2.0 mA cm −2 , with an area capacity of 2.0 mAh cm −2 After 100 h of electroplating / stripping under the same conditions, lithium dendrites were clearly formed on the bare lithium surface of the comparative example, and the dendrites showed a loose porous structure, which indicated the inhomogeneity in the lithium deposition process. In contrast, the surface of the novel thin lithium negative electrode in Example 5 was very flat and dense, further confirming that the lithium-rich lithium-philic alloy interface promoted the uniform deposition of lithium and effectively suppressed the formation of lithium dendrites. In addition, the modified lithium metal negative electrode has a lower ion diffusion barrier, and the insulating component LiNO3 in the alloy layer ensures the rapid diffusion of lithium ions on the surface and internal direction of the negative electrode, suppressing the growth of dendrites caused by the uneven local ion distribution under high current density.

[0046] Figure 5 Comparative Example and Example 4 in LiǁLiNi 0.83 Mn 0.12 Co 0.05 Electrochemical impedance spectroscopy in O2 battery. In 1M LiPF6 EC / EMC (v / v = 3:7) and electrolyte containing 2% VC, EIS was used to evaluate the changes in the interface characteristics of the new lithium metal anode / electrolyte with a lithiophilic interface alloy phase. The full battery test was performed after two cycles of activation at 0.1C, and then charged at 0.1C and discharged at 0.3C. The spectra of the comparative example and the embodiment are composed of a high-frequency semicircle, a medium-frequency 1 / 4 circle, and a low-frequency irregular circle, respectively, corresponding to the charge transfer resistance ( R ct )、SEI film impedance( R SEI ) and diffusion impedance. In particular, the high frequency Z' value is defined as R s, which corresponds to the interface impedance caused by side reactions and dendrite growth. The semicircle of the high frequency of the novel lithium negative electrode in the embodiment is obviously smaller than that of the bare lithium in the comparative example, indicating that the full battery assembled with the bare lithium in the comparative example experienced more intense internal side reactions and dendrite growth during the test. In addition, the modified lithium metal negative electrode has a higher electrical conductivity, and the low diffusion barrier of the interface alloy layer significantly increases the diffusion rate of lithium atoms on the surface, improves the tolerable current density of the negative electrode and reduces the probability of dendrite growth.

[0047] Figure 6 Comparative Example and Example 5 in LiǁLiNi 0.83 Mn 0.12 Co 0.05 Long-cycle performance in an O2 battery. The cathode tested in a full cell has a 20 mg cm -2 The test conditions were 0.1C activation for two cycles, followed by 0.1C charging and 0.3C discharge. 0.83 Mn 0.12 Co 0.05 The O2 full battery showed more than 210 stable cycles with a capacity retention rate of 89.92% and a surface capacity of 4.0 mAh cm -2 . Although the electrolyte-induced resistive SEI accumulates during lithium plating / stripping in the early stages of battery cycling, the lithium-rich lithium-philic alloy interfacial layer homogenizes the lithium ion flux, thereby inducing uniform lithium deposition and minimizing the appearance of lithium dendrites. Therefore, no obvious capacity drop and sudden battery death are observed during cycling. On the contrary, the unstable interface between bare lithium and electrolyte accelerates the exposure and growth of fresh lithium dendrites, leading to rapid depletion of the lithium negative electrode. The continuous formation of dead lithium in the Bare-Li negative electrode and the continuous consumption of limited electrolyte during cycling seriously affect the ion transport, resulting in a sharp drop in battery capacity. Bare-Li||LiNi 0.83 Mn 0.12 Co 0.05 The capacity of the O2 full cell decays rapidly after only 18 cycles, indicating the interfacial instability between the unmodified bare lithium anode and the ester electrolyte.

[0048] Figure 7 (a) Comparative Example and (b) Example 5 in LiǁLiNi 0.83 Mn 0.12 Co 0.05The charge and discharge curves of different cycles in the O2 battery. The test conditions are to activate it at 0.1C for two cycles, then charge it at 0.1C and discharge it at 0.3C. Compared with the bare lithium in the comparative example, the new battery in the embodiment still shows an excellent ability to maintain its original potential distribution even after 200 cycles of charge and discharge. This is mainly attributed to the improved interface stability of the negative electrode containing the new alloy interface layer of Li-Cu and LiNO3, which realizes the rapid transmission and diffusion of lithium ions in the new alloy interface layer. The unstable interface of bare lithium accelerates the growth of lithium dendrites, causing the battery charge and discharge performance to drop rapidly within 40 cycles.

[0049] (III) Effectiveness test: The chemical replacement method for preparing a new lithium metal negative electrode has the advantages of being simple and scalable. In order to further explore the actual operation of the new lithium metal negative electrode in a traditional low-cost carbonate electrolyte, the present invention uses a lamination process to assemble a high specific energy lithium metal soft-pack battery under dry room conditions and conducts a cycle test. The method is as follows: In a drying room with a moisture content below 1‰, the coating loading was 20-25 mg cm −2 The coated positive electrode was placed in a vacuum oven to dry overnight and then punched into square pole pieces. Subsequently, the lithium ribbon with an interfacial lithium-titanium alloy layer on both sides after chemical replacement was punched into negative electrode pieces and assembled with the positive electrode to form a battery with an energy density of 400 Wh kg −1 Lithium metal soft pack battery. The specific details are as follows: prepare 15 double-sided positive electrodes, 2 single-sided positive electrodes and 16 double-sided negative electrodes, use a separator to alternately wrap one positive electrode and one negative electrode, place 2 single-sided positive electrodes on the outside of the battery cell, put the stacked battery cell into an aluminum-plastic film for three-sided sealing, inject 1M LiPF6 EC / EMC (v / v = 3:7) and electrolyte containing 2% VC, and then vacuum seal all directions. The soft pack test was carried out under 0.1C charging and 0.3C discharge conditions after two cycles of 0.1C activation.

[0050] Figure 8 The comparative example and Example 4 were at 400 Wh kg −1 Long cycle performance diagram in soft pack battery. The capacity is 5.74Ah, and the embedded picture is an optical photo of the finished soft pack battery. The cycle stability of the soft pack battery assembled with the new lithium negative electrode of Example 4 is significantly improved, with an N / P ratio as low as 1.02 and a lean electrolyte of 1.75 g Ah. −1 400 Wh kg −1The soft-pack battery still showed a capacity retention rate of 96.04% after 100 cycles. In contrast, the soft-pack battery using bare lithium as the negative electrode showed rapid decay from the beginning of the cycle and dropped to 1.86 Ah after 16 cycles. The soft-pack test results show that the application of the new lithium negative electrode in the embodiment to the ester electrolyte can still effectively improve the cycle stability of practical lithium metal batteries. The above invention proves that the economical and simple chemical replacement method for treating lithium metal has great potential in achieving a stable negative electrode interface.

[0051] Fig. 9 It is a reaction mechanism diagram of the comparative example and Example 4 during the electroplating process. The surface of the lithium foil produced by the scraping or rolling process in the drying room is uneven and contains oxidizing substances, so a large number of lithium dendrites are rapidly generated during the cycle, resulting in a short circuit in the battery or difficulty in cycling. However, the surface of the new thin lithium negative electrode that has been chemically repaired and chemically replaced is uniform and flat. Lithium ions quickly pass through the Li-Ti new alloy interface layer during the electroplating stripping process and are densely and evenly deposited under the alloy layer, avoiding the growth of dendrites and achieving a long cycle.

[0052] The above is only a preferred implementation method of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements made without departing from the technical principles of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a thin lithium negative electrode adapted to a traditional low-cost ester electrolyte, characterized in that: The lithium foil is chemically repaired using a chemical repair agent, and the chemically repaired lithium foil is immersed in a lithium-philic metal salt solution for chemical replacement, cleaning, and drying to obtain a lithium metal negative electrode with a lithium-philic interface alloy phase.

2. The preparation method according to claim 1, characterized in that: The chemical repair agent is any one of dimethyl sulfoxide, tetrahydrofuran, N-methylformamide, N,N-dimethylformamide, acetone, acetonitrile and fluoroacetonitrile, or a mixture of any two or more in any proportion. The chemical repair agent needs to be dried before use.

3. The preparation method according to claim 1, characterized in that: The lithium-philic metal salt in the lithium-philic metal salt solution is any one of TiCl4, InCl3, In(NO3)3 and Cu(NO3)2, or a combination of two or more thereof; the lithium-philic metal salt solution and the solvent used for cleaning are any one of ethylene glycol dimethyl ether, dodecyl ether, cyclopentyl methyl ether, 1,3-dioxolane, ethylene carbonate and ethyl methyl carbonate, or a combination of two or more thereof, and the lithium-philic metal salt and the solvent must be dried before use.

4. The preparation method according to claim 1, characterized in that: The concentration of the lithium-philic metal salt in the lithium-philic metal salt solution is 1-100 mM, and the time of chemical replacement is 1-60 minutes.

5. The preparation method according to claim 1, characterized in that: The time for chemical repair is 0.2~2 h.

6. The preparation method according to claim 1, characterized in that: Chemical repair, chemical replacement, and drying were all performed in an argon-filled glove box.

7. The thin lithium negative electrode adapted to low-cost ester electrolyte obtained by the preparation method according to any one of claims 1 to 6, wherein the thickness of the lithium foil is 20 to 50 microns and the thickness of the protective layer is 1 to 10 microns.

8. The use of a thin lithium negative electrode adapted to a low-cost ester electrolyte in a lithium metal battery according to claim 7, characterized in that: It comprises a positive electrode, a lithium metal negative electrode as claimed in claim 7, a separator and an ester electrolyte containing a lithium salt; the lithium salt in the ester electrolyte is one or more of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium tetrafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide and tris(trifluoromethylsulfonyl)methyl lithium; the solvent in the ester electrolyte is one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, fluoroethylene carbonate, ethyl methyl carbonate, vinylene carbonate or dimethyl carbonate; the concentration of the lithium salt in the solvent is 0.5-4 mol / L.

9. The use according to claim 8, characterized in that: The lithium metal battery is a symmetrical battery, a full battery or a soft pack battery, and one common formula of the electrolyte is 1M LiPF6 EC+EMC electrolyte, and the volume ratio of EC to EMC is 3:

7.

10. The use according to claim 9, characterized in that: When lithium metal batteries are full cells and soft pack batteries, the positive electrode loading is 20-25 mg cm −2 High nickel ternary material LiNi 0.83 Mn 0.12 Co 0.05 The assembly of O2, symmetric cells and full cells was carried out in a glove box filled with argon, and the assembly of soft-pack cells was carried out in a dry room with a moisture content of less than 1‰.

Citation Information

Patent Citations

  • A composite lithium metal anode, its preparation method and application

    CN113629236B

  • Lithium metal negative electrode and preparation method and application thereof

    CN113437258A

  • Preparation method of artificial protective layer of lithium metal negative electrode

    CN113594423A